Progress on long non-coding RNAs in calcific aortic valve disease - Yan Shen; Jiahui Li; Zehao Zhao; Xiaomin Chen (Frontiers in Cardiovascular Medicine)
Calcific aortic valve disease (CAVD) is a common cardiovascular condition in the elderly population. The aortic valve, influenced by factors such as endothelial dysfunction, inflammation, oxidative stress, lipid metabolism disorders, calcium deposition, and extracellular matrix remodeling, undergoes fibrosis and calcification, ultimately leading to stenosis. In recent years, long non-coding RNAs (lncRNAs) have emerged as significant regulators of gene expression, playing crucial roles in the occurrence and progression of various diseases. Research has shown that lncRNAs participate in the pathological process underlying CAVD by regulating osteogenic differentiation and inflammatory response of valve interstitial cells. Specifically, lncRNAs, such as H19, MALAT1, and TUG1, are closely associated with CAVD. Some lncRNAs can act as miRNA sponges, form complex regulatory networks, and modulate the expression of calcification-related genes. In brief, this review discusses the mechanisms and potential therapeutic targets of lncRNAs in CAVD.